THE INFLUENCE OF COMMUNITY SOCIAL CAPITAL ON POVERTY IN THE NORTHERN COASTAL AREA OF NGEMPLAKREJO SUBDISTRICT, PASURUAN CITY - Teguh Adhipati; Agustina Nurul Hidayati; Ardiyanto Maksimilianus Gai (Universitas KH. Abdul Chalim Mojokerto, 2025)
In general, social capital is characterised by the existence of social relationships, trust and social networks in the community. This is a very important thing in the progress of material benefits and welfare. Social capital is seen as a value of mutual trust, between community members and their leaders involving social networks of social norms, and social trust that encourages social collaboration for a common interest. Where social capital is believed to be able to overcome poverty. Ngemplakrejo Village is one of the villages in Pasuruan City that has a poor population, namely there are 1,000 residents, even almost half of the number of poor people are working as fishermen. Therefore, the purpose of this study is to see the influence between community social capital on poverty in the North Coastal Region of Pasuruan City, namely in Ngemplakrejo Village. The research method in this study is to use quantitative methods. Where in this study will explain the effect of social capital on poverty in Ngemplakrejo Village using the Chi-Square test effect analysis, in the SPSS version 2.6 application. The results showed that social capital in the cooperation variable has an influence on poverty parameters, namely fishermen's education with a significance value of 0.018; then the fishermen's economy with a significance of 0.000 and fishermen's living standards with a significance of 0.011. In addition, social network has an influence on poverty parameters, namely fishermen's education with a significance value of 0.004 and fishermen's economy with a significance value of 0.000.